Pengaruh Profitabilitas, Leverage, dan Sales Growth terhadap Tax Avoidance - Luh Nadi; Michell Silvia (Jurnal Ekonomi Manajemen Akuntansi, 2026)
This study aims to analyze and obtain empirical evidence regarding the effect of profitability, leverage, and sales growth on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. This research method uses a quantitative approach with secondary data in the form of annual financial reports obtained from the official IDX website and related company websites. The sampling technique used a purposive sampling method to obtain a sample of companies that met the research criteria during the observation period. The dependent variable in this study is tax avoidance, which is proxied by the Effective Tax Rate (ETR), while the independent variables consist of profitability as measured by Return on Assets (ROA), leverage as measured by the Debt to Equity Ratio (DER), and sales growth as measured by annual sales growth. The data analysis technique uses panel data regression through the stages of selecting the best model, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that profitability, leverage, and sales growth simultaneously influence tax avoidance. Partially, profitability influences tax avoidance, while leverage and sales growth do not.